Long memory and changing persistence - Robinson Kruse; Philipp Sibbertsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
We study the empirical behaviour of semi-parametric log-periodogram estimation for long memory models when the true process exhibits a change in persistence. Simulation results confirm theoretical arguments which suggest that evidence for long memory is likely to be found. A recently proposed test by Sibbertsen and Kruse (2009) is shown to exhibit noticeable power to discriminate between long memory and a structural change in autoregressive parameters.
Keywords: C12; C22; 330; Long memory; changing persistence; structural break; semi-parametric estimation; Schätztheorie; Strukturbruch; Theorie